2011
DOI: 10.1124/jpet.111.182816
|View full text |Cite
|
Sign up to set email alerts
|

Afobazole Modulates Microglial Function via Activation of Both σ-1 and σ-2 Receptors

Abstract: Microglial cells play a critical role in the neuroinflammatory response that accompanies various diseases of the central nervous system, such as ischemic stroke, and ATP is a major signaling molecule regulating the response of these cells to these pathophysiological conditions. Experiments were carried out to determine the effects of afobazole on microglial function and to identify the molecular mechanisms by which afobazole affects microglial cells. Afobazole was found to inhibit migration of microglial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 34 publications
(46 reference statements)
4
76
2
Order By: Relevance
“…Taken together, our data suggest that afobazole acts as a -receptor agonist and that it specifically activates -1 receptors. Additional data collected in our laboratory suggests that afobazole may also act as a -2-receptor agonist (Cuevas et al, 2011). Given that neither metaphit nor the -1-receptor-selective antagonists completely eliminated the effects of afobazole, the possibility exists that this drug is also acting via mechanisms other than receptors to prevent [Ca 2ϩ ] i overload.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data suggest that afobazole acts as a -receptor agonist and that it specifically activates -1 receptors. Additional data collected in our laboratory suggests that afobazole may also act as a -2-receptor agonist (Cuevas et al, 2011). Given that neither metaphit nor the -1-receptor-selective antagonists completely eliminated the effects of afobazole, the possibility exists that this drug is also acting via mechanisms other than receptors to prevent [Ca 2ϩ ] i overload.…”
Section: Discussionmentioning
confidence: 99%
“…The current study shows that p-BrDPhG also inhibits microglial activation, and this DTG analog is 4-fold more potent than the parent compound and a second pan-selective s agonist, afobazole (Hall et al, 2009;Cuevas et al, 2011b). Unlike ischemia-and acidosis-evoked [Ca 21 ] i dysregulation, which appears to be exclusively affected by s-1 receptor activation, both s-1 and s-2 receptors can modulate microglial migration (Cuevas et al, 2011b).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, our laboratory showed that activation of s receptors with pan-selective ligands, such as o-DTG or afobazole, modulates microglial activation and inhibits microglial cell migration in response to chemoattractants, such as ATP (Cuevas et al, 2011b). This effect on microglial cell ] i (6S.E.M.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations